Runoff Variation due to Landuse Change in Small Watershed of Western Ghats Calicut District, Kerala - Hakkim, V.M. Abdul; Nandakumar, V.; Sajeena, S. (Journal of Soil and Water Conservation, 2022)
Three small mono-culture watersheds, planted with cashew, coffee, tea and one small watershed with dense forest of Western Ghats. Analysis of the rainfall and runoff data indicated that nearly 50% of the total rainfall leaves from the mono-culture watershed as runoff, whereas the runoff from dense forested watershed is only about 30% of the rainfall.